Commercial Activity Business Processes Reengineering: Theoretical, Methodological and Practical Aspects - TEPLOV, Vitaly Ivanovich; TARASOVA, Elizaveta Evgenievna; MATUZENKO, Elena Viktorovna; ALYABIEVA, Marianna Vladimirovna; BELENOV, Oleg Nikolaevich (Journal of Advanced Research in Law and Economics, 2016)
Reengineering is an integrity of means, measures and methods for cardinal improvement of the main indicators of company’s activity. The analysis and subsequent changes of the existing business processes are carried out with this view. Reengineering project includes a number of interconnected stages: from the development of the image of a future company’s business and schematic consideration of its future competitive strategy to the realization of the developed competitive strategy and introduction of new business processes at a company. Reengineering is the integrity of means, measures and methods including the corresponding information technologies, aimed at cardinal improvement of a company’s activity main indicators. In order to achieve considerable improvement of the existing company’s activity indicators reengineering presupposes fundamental changes in the existing business processes. That is why reengineering methods can be used by a company in the innovative strategy development. The innovative character of reengineering is in the introduction at a company of principally new business processes, aimed at, first of all, creating, mastering and application of technological innovations. The goal of the article is to form and analyze the peculiar features of commercial activity business processes reengineering. The authors have analyzed the techniques of business processes reengineering conducting. The article provides requirements to project companies, which conduct reengineering. A special attention is paid to the stages of reengineering. Instrumental means, used in business processes reengineering are analyzed in detail.